Benedetto cotrugli on double entry Bookkeeping - Alan Sangster; Franco Rossi (De Computis, 2018)
(Benedetto Cotrugli sulla contabilità in Partita Doppia) In 1458, a former international merchant, Benedetto Cotrugli, wrote a 200-page manual on how to be a successful merchant: Libro de Larte dela Mercatura (Book of the Art of Trade). It included a 5-page chapter on double entry bookkeeping, something never previously preserved in written form. The earliest known copy of this book dates from 1475. This paper provides an overview of the book and of Cotrugli; and it presents new English and Italian translations of Cotrugli’s chapter on double entry bookkeeping. These differ from previous translations in that they are based solely on the earliest copy of Cotrugli’s book from 1475. The English translation is also the first to have been prepared by an accountant enabling the description of entries in account books to be in the form Cotrugli intended. This is the first of two contributions made by this paper. The second is that it identifies Cotrugli’s chapter as a first stage in the training of a bookkeeper, where a broad introduction to the subject is laid down as a foundation for further study or practical experience.